2012
DOI: 10.12659/msm.882908
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in E-selectin and ICAM-1: Relation to Atherosclerosis

Abstract: SummaryBackgroundThis study aimed to investigate the association of both intercellular adhesion molecule-1 (ICAM-1) and endothelial cell adhesion molecule (E-selectin) polymorphisms using PCR technique and their role in the pathogenesis of atherosclerosis.Material/MethodsThe study enrolled 285 individuals, classified into 4 groups: 63 cerebrovascular atherosclerotic patients, 75 cardiovascular patients, 72 peripheral atherosclerotic patients and 75 normal healthy individuals.ResultsThe frequency of the mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
(40 reference statements)
0
15
0
1
Order By: Relevance
“…The mechanisms of the proinflammatory effects of ICAM-1 on endothelial cells might be that ICAM-1 binds and interacts with leukocyte integrin receptors such as lymphocyte function-associated antigen-1 LFA-1 and Mac-1 [41] . ICAM-1 also serves as a receptor for soluble fibrinogen, which mediates leukocyte adhesion to the endothelium through an ICAM-1 dependent pathway [42] . Study from Kanter et al [43] demonstrated that cPKCβII mediates insulin resistance in part by stimulating threonine phosphorylation of the PI3K, which in turn blunts insulin-stimulated Akt-eNOS activation and then upregulates the expression of VCAM-1 and ICAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of the proinflammatory effects of ICAM-1 on endothelial cells might be that ICAM-1 binds and interacts with leukocyte integrin receptors such as lymphocyte function-associated antigen-1 LFA-1 and Mac-1 [41] . ICAM-1 also serves as a receptor for soluble fibrinogen, which mediates leukocyte adhesion to the endothelium through an ICAM-1 dependent pathway [42] . Study from Kanter et al [43] demonstrated that cPKCβII mediates insulin resistance in part by stimulating threonine phosphorylation of the PI3K, which in turn blunts insulin-stimulated Akt-eNOS activation and then upregulates the expression of VCAM-1 and ICAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, a relationship between HCY and cardiovascular status in patients with mood disorders has not been studied so far. Recently, proteins such as E-selectin and intracellular adhesion molecule-1 (ICAM-1) were considered as markers of endothelial functions and postulated as involved in genetic predisposition to atherosclerosis [10]. Therefore, it would be of interest to know how HCY relates to the markers of endothelial functions in patients with mood disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 20 studies included, only 6 were Caucasian studies, which may have affected the true association of Caucasian ICAM-1 polymorphism with ischemic stroke. (Flex et al, 2004;Li et al, 2009;Mohy et al, 2015;Motawi et al, 2012;Pola et al, 2003;Volcik et al, 2010). Thus, additional studies with larger cohorts are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies were from China (Geng, 2011;Guo, Liu, & Guo, 2011;Huihua et al, 2016;Li et al, 2009;Liu, 2005;Shang, 2004;Sun & Zhang, 2005;Sun, Wu, & Deng, 2009;Wang et al, 2015;Wei, Liu, Huang, Tang, & Meng, 2005;Xing, Song, Hongjun, & Zhang, 2006;You, Huang, & Liu, 2007;Zhang, Cheng, Peng, Wang, & Peng, 2007;Zhang & Zhang, 2012;Zhou, Zhu, & Sun, 2007), two studies were from Italy (Flex et al, 2004;Pola et al, 2003), two studies from Egypt (Mohy, Ali, & Omar, 2015;Motawi, Shaker, Taha, & Abdel Raheem, 2012), one study was from the United States (Volcik, Ballantyne, Hoogeveen, Folsom, & Boerwinkle, 2010). Caucasian subjects were included in six studies (Flex et al, 2004;Geng, 2011;Mohy et al, 2015;Motawi et al, 2012;Pola et al, 2003;Volcik et al, 2010), black subjects were included in one (Volcik et al, 2010), and Asians were included in rest of the studies. The publication date ranged from 2003 (Pola et al, 2003) to 2016 (Huihua et al, 2016).…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation